The Value of MR-DWI and T1 Mapping in Indicating Radiation-Induced Soft Tissue Injury - Wang, Zeng; Xiong, Bowen; Kang, Nannan; Pan, Xiaoxian; Wang, Caihong; Su, Li; Xing, Zhen; Hong, Jinsheng (Frontiers in Oncology, 2021)
C57BL/6 mice were randomly divided into control group (Nor group), irradiation group (IR group) and irradiation plus glycyrrhetinic acid group (GA group). The IR group and GA group were treated with 6MV X-rays to irradiate the right hind limbs of mice for 30 Gy in a single shot. MRI examinations were performed before and on the 7th day after irradiation to measure the apparent diffusion coefficient (ADC) value and the longitudinal relaxation time(T1) value of the hind limb muscles of the mice. On the 90th day after irradiation, the hind limb contracture was measured, and the right hind limb muscle was taken for HE staining, masson staining, immunohistochemical staining and Western blot analysis to detect the expression of a-SMA and Fibronectin. ②The other 30 mice were grouped as randomly as above. On the 7th day after irradiation, the right hind limbs of the mice were examined by MRI to measure the ADC value and T1 value of the thigh muscles, and then the right hind thigh muscles were immediately sacrificed to detect IL-1β, IL-6, TNF-a and TGF-β1 expression with ELISA.The results show that ADC value and T1 value were correlated with the degree of contracture on Day 90 after irradiation，also positively correlated with the fibrosis index and inflammatory factors.The MR-DWI and T1mapping values on the 7th day after irradiation can reflect the early condition of tissue inflammation after the soft tissue is irradiated; and the values have a certain correlation with the degree of radiofibrosis of the soft tissue in the later period, and thus can be used as an index to predict radiofibrosis.